N-doped carbon nanofibers with internal cross-linked multiple pores for both ultra-long cycling life and high capacity in highly durable K-ion battery anodes. (20th March 2020) - Zhang, Shenkui; Xu, Zhiguang; Duan, Huanhuan; Xu, Anding; Xia, Qi; Yan, Yurong; Wu, Songping
Abstract: Potassium-ion batteries are of utmost interest to researchers as emerging energy storage device due to abundant resource and high safety. However, they've been suffering low reversible capacity, poor rate and unreliable cycling stability during potassiation/depotassiation because of larger size of potassium ion. Here, for the first time, a sustainable and low-cost resource, i.e., renewable acrylic yarn, as raw materials were used to prepare N -doped mesoporous carbon nanofibers (NMCNFs) by using facile electrospinning then followed with "high temperature self-fluid technology". The consequent internal cross-linked multiple pores and high nitrogen-doping emerged in elaborately carved N -doped mesoporous carbon nanofibers, providing sufficient active-sites and shortened ion diffusion paths. The resultant NMCNFs delivered an impressively reversible capacity of 351.1 mAh g −1 after 500 cycles at a current density of 200 mA g −1, outstanding rate performance of 134 mAh g −1 at 10 A g −1 . Even at a high rate of 5 A g −1, reversible capacity of 122.3 mAh g −1  has been enduringly retained after 20, 000 cycles. The result of the density functional theory (DFT) calculations revealed the pyridinic/pyrrolic N -doping could effectively enhance the adsorption of K + to the NMCNFs electrode, which boosted the K-ion storage capability of NMCNFs. Such excellent attributes above make NMCNFs to be a promising low-cost and environment-friendly anode for next-generation potassium-ion rechargeable batteries.